Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1097/00006842-196909000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Cardiac Rate Regulation in Preweanling Rats

Abstract: Cardiac rate was recorded by lightweight leads from unrestrained pups under 4 conditions: in the home cage litter situation, while being picked up by the experimenter, during 6 min alone in a novel environment, and in response to a startle stimulus. Resting heart rates in the litter showed evidence of high sympathetic activity during the second week of life; cardiac responses to stimulation were consistently deceleratory. By 20 days, the adult pattern of low resting rates and tachycardia upon stimulation had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
60
1

Year Published

1972
1972
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 10 publications
10
60
1
Order By: Relevance
“…For instance, the heart rate of young rats (P3-P5) does not respond to handling stress, while older rats (P6-P16) show a decreased heart rate in response to handling stress (Hofer and Reiser, 1969). The heart rate response reaches an adult state only after P20, when handling elicits an increase in heart rate (Hofer and Reiser, 1969).…”
Section: Neonatal Development Of Other Autonomic Control Systemsmentioning
confidence: 99%
“…For instance, the heart rate of young rats (P3-P5) does not respond to handling stress, while older rats (P6-P16) show a decreased heart rate in response to handling stress (Hofer and Reiser, 1969). The heart rate response reaches an adult state only after P20, when handling elicits an increase in heart rate (Hofer and Reiser, 1969).…”
Section: Neonatal Development Of Other Autonomic Control Systemsmentioning
confidence: 99%
“…Thus, during the first 2 weeks or so of life, spontaneous gross motor movements in rats were observed in the absence of corresponding changes in HR (Ashida, 1972;Hofer & Reiser, 1969), suggesting that the two systems may develop at different rates. A specific classically conditioned HR CR was established in 3-4-day-01d rats (L. T. Martin & Alberts, 1982), but the question of possible motor involvement was not evaluated.…”
mentioning
confidence: 99%
“…On the other hand, the developmental change in HR follows a different time course in small animals. In rats, HR increases from ϳ300 beats/min at birth to ϳ500 beats/min at ϳ1 mo of age (15,37). HR of anesthetized newborn mice (rats) also increases from ϳ360 (ϳ340) to ϳ440 (ϳ490) beats/min during the first postnatal week (17,26).…”
mentioning
confidence: 99%
“…This is because stressor stimuli due to the attachment of ECG electrodes produce a sympathetically and/or parasympathetically mediated response in HR. It has been shown that there is a series of stages by which HR responsiveness to stressor stimuli becomes established during the first few postnatal weeks (7,15,16,18,23,31). According to the pioneering work by Hofer and Reiser in 1969 (15), HR is unresponsive to stressor stimuli in the first few days but decreases between 6 and 16 days of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation